The complete mitochondrial genome of Sphenomorphus indicus (Reptilia: Scincidae) - Xin-Sheng Tang; Dian-Cheng Yang; Ya-Juan Lin; Liang-Liang Dai (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome (mitogenome) sequence of Sphenomorphus indicus was sequenced and characterized by next-generation sequencing technology. The total length of mitogenome is 17,027 bp and contains 13 protein-coding genes, 22 tRNA genes, 2 ribosome RNA genes, and 2 non-coding regions (the control region and the putative L-strand replication origin). Most of the genes of S. indicus are encoded on the H-strand, except for the ND6 subunit gene and 8 tRNA genes which is distributed on the L-strand. Phylogenetic reconstruction suggested that S. indicus is the sister group of the S. incognitus within the genus Sphenomorphus. The complete mitochondrial genome sequence presented here will be useful to study the evolutionary relationships and genetic diversity of S. indicus.